Gas‐Generating Nanoplatforms: Material Chemistry, Multifunctionality, and Gas Therapy. Issue 49 (31st July 2018) - Yu, Luodan; Hu, Ping; Chen, Yu
Abstract: The fast advances of theranostic nanomedicine enable the rational design and construction of diverse functional nanoplatforms for versatile biomedical applications, among which gas‐generating nanoplatforms (GGNs) have emerged very recently as unique theranostic nanoplatforms for broad gas therapies. Here, the recent developments of the rational design and chemical construction of versatile GGNs for efficient gas therapies by either exogenous physical triggers or endogenous disease‐environment responsiveness are reviewed. These gases involve some therapeutic gases that can directly change disease status, such as oxygen (O2 ), nitric oxide (NO), carbon monoxide (CO), hydrogen (H2 ), hydrogen sulfide (H2 S) and sulfur dioxide (SO2 ), and other gases such as carbon dioxide (CO2 ), dl ‐menthol (DLM), and gaseous perfluorocarbon (PFC) for supplementary assistance of the theranostic process. Abundant nanocarriers have been adopted for gas delivery into lesions, including poly(d, l ‐lactic‐ co ‐glycolic acid), micelles, silica/mesoporous silica, organosilica, MnO2, graphene, Bi2 Se3, upconversion nanoparticles, CaCO3, etc. Especially, these GGNs have been successfully developed for versatile biomedical applications, including diagnostic imaging and therapeutic use. The biosafety issue, challenges faced, and future developments on the rational construction of GGNs are also discussed for further promotion of their clinical translation to benefit patients. Abstract : The construction of gas‐generating nanoplatforms (GGNs) plays the determining role for precise gas therapy. The recent developments of the rational design and chemical construction of versatile GGNs for efficient gas therapies are summarized. The biosafety issue, challenges faced, and future developments on the rational construction of GGNs are also discussed for further promotion of their clinical translation.